IMPLEMENTASI KEBIJAKAN PENANGANAN PRASARANA DAN SARANA UMUM (PPSU) PADA KEBERSIHAN TINGKAT KELURAHAN PADEMANGAN BARAT JAKARTA UTARA - Maryanti; Tulus Santoso (Institut Ilmu Sosial dan Manajemen STIAMI, 2025)
Implementation of policies for handling public infrastructure and facilities Handling Public Infrastructure and Facilities (PPSU) is work that needs to be done immediately and cannot be postponed because it can result in losses, dangers and disrupt the interests of the public/community and in order to speed up the functioning of locations/infrastructure and public facilities/assets as well as regional assets that are damaged, dirty and/or disturbing according to their intended purpose. This research uses qualitative research with qualitative descriptive methods. This research uses two theories from Ripley and Franklin, namely the level of compliance, measures of routine fluency and desired impact. The results of this research are that there is still a lack of public awareness in maintaining environmental cleanliness and the community still relies on PPSU officers to clean the environment of West Pademangan subdistrict. And the officers still lack socialization. Keywords Policy implementation, Handling Public Infrastructure and Facilities (PPSU)